This section requires Javascript.
You are seeing this because something didn't load right. We suggest you, (a) try
refreshing the page, (b) enabling javascript if it is disabled on your browser and,
finally, (c)
loading the
non-javascript version of this page
. We're sorry about the hassle.
This sum is an infinite geometric series of the form n = 1 ∑ ∞ x n with x = ϕ 1 .
Since ∣ x ∣ < 1 we know that this sum simplifies to
1 − x x = 1 − ϕ 1 ϕ 1 = ϕ − 1 1 = 2 1 + 5 − 1 1 = 5 − 1 2 ∗ 5 + 1 5 + 1 = 2 5 + 1 = ϕ .
(Note that ϕ 2 − ϕ − 1 = 0 ⟹ ϕ − 1 = ϕ 1 ⟹ ϕ − 1 1 = ϕ , so we could have skipped the last bit of algebra.)